Formation, mitigation and analysis of 3-MCPD and glycidyl esters during deep-fat frying of potato chips and chicken breast meat using RBD palm olein - Wong, Yu Hua (2016)
3-monochloro-1,2-propanediol (3-MCPD) esters and glycidyl ester (GE) are thermally induced contaminants formed during high-temperature processes, such as deep-fat frying (DFF). In this study, the levels of 3-MCPD esters and GE formed during the frying of carbohydrate-rich and protein-rich foods in different frying systems, the effect of antioxidants, and alternative determination method of 3-MCPD esters were studied. This study was divided into four parts. First, potato chips (a carbohydrate-rich food) were fried in palm olein under different parameters for 5 days. The applied frying temperatures used were 160 °C and 180 °C, and the concentrations of NaCl were 0%, 1%, 3% and 5%. The formation and changes of 3-MCPD esters and GE levels and the oxidative stability of palm olein during DFF were investigated. A high frying temperature resulted in a high level of 3-MCPD esters but a low level of GE. A long frying duration caused a reduction in 3-MCPD esters and an increase in GE. The addition of NaCl to the frying system significantly (p < 0.05) increased the level of 3-MCPD esters, but no significant difference (p > 0.05) was observed for the GE content. The frying oils and the oils extracted from the potato chips showed similar results. The oil qualities were within the safety limit after 5 days of frying. Second, chicken breast meats (CBM, a protein-rich food) were fried in palm olein under the same frying conditions mentioned earlier. In general, the result showed similar trends to the frying of carbohydrate-rich food. However, the levels of 3-MCPD esters and GE were higher than those of the potato chips. This is because CBM contains transition metals, such as iron that can accumulate in frying oils, which can further enhance the degradation rate of the oils.